A system of molecular markers to identify alleles of the Rht-B1 and Rht-D1 genes controlling reduced height in bread wheat - I. V. Porotnikov; O. P. Mitrofanova; O. Yu. Antonova (Вавиловский журнал генетики и селекции)
Mutant alleles of the Rht-B1 and Rht-D1 (Reduced height) genes are widely used in bread wheat breeding for the development of intensive-type cultivars. These genes and their f lanking regions have been sequenced and the point mutations leading to the nonsense codons (Rht-B1b, Rht-B1e, Rht-B1p and Rht-D1b alleles) and various insertions (Rht-B1c, Rht-B1h and Rht-B1i-1) associated with a change in plant height have been described. DNA-markers based on the allele-specif ic PCR have been developed to identify single-nucleotide changes. However, the use of such technique imposes stringent PCR conditions, and the resulting data are not always unambiguous. An alternative can be found in the CAPS technology: it detects differences in sequences by digesting PCR products. In the absence of restrictases capable of digesting DNA at the point mutation site, restriction sites can be introduced into the primer sequence (derived CAPS). The aim of this study was to propose a system of CAPS-, dCAPS- and STS-markers for identifying alleles of the reduced height genes frequently used in breeding programs. Three CAPS have been developed to identify the Rht-B1b, Rht-D1b, Rht-B1p alleles, as well as two dCAPS for Rht-B1b, Rht-B1e. STS-markers for the insertioncontaining alleles Rht-B1c, Rht-B1h and Rht-B1i-1 have been selected from publications. The proposed markers were tested during the genotyping of 11 bread wheat accessions from the VIR collection with the abovementioned mutant alleles and the wild-type Rht-B1a and Rht-D1a. The presence of nonsense mutations was also conf irmed by the results of allele-specif ic PCR. This marker system, along with the existing ones, can be used to identify dwarf ing alleles of the Rht-B1 and Rht-D1 genes in bread wheat for genetic screening of accessions from ex situ collections and/or for marker-assisted selection.